COMPARISON AND EVALUATION ON THE WAR ON TERROR: REALISM, LIBERALISM, AND FEMINISM IN INTERNATIONAL RELATIONS THEORY - Ahmad Fuad Fanani (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2026)
The emergence of global-network terrorism threats marks a new turn of world politics agenda. The terrorist attack on World Trade Center, New York and the Pentagon, Washington on 9/11/2001 became the iconic event. This event caused significant impacts on the US foreign and defense policies toward the global world. The War on Terror emerged as a new vocabulary in the world politics and shapes the new international security agenda in the Post Cold War era. The War on Terror changed the relations between states, particularly in shaping the alliance and re-alliance between the US and other countries such as in the building of the “coalitions of the willing”. Although terrorism has been placed as the new enemy and threat for national and global security, there is a debate on the definition, legality, and strategies of war on terrorism. It is no doubt, therefore, that the War on Terror is one of the contemporary agendas of world politics. This article will examine and analyze the War on Terror by applying three theoretical traditions of International Relations, namely Realism, Liberalism, and Feminism.